A Fisiografía e sua paisagem na busca da personalidade do lugar - Yázigi, Eduardo (Paisagem e Ambiente, 1998)
Here, the main idea concerns to support physiography as the best way to keep locals identities. In fact, actually we verify strong features that are removing traditionals characteristics: mobilities for working (and so som e ethnical mixture); modern techniques and new material on building; information producing new patterns through television, etc. Under these conditions, the day life and consequently the tourism subject become less genuine. In this case, physical aspects of geography could be the strongest vectors to preserve landscape, because they are relatively stable. Also, respect to natural order can create a unique solution on land use, in the sen se that a cottage on the rain forest is not a cottage on ucranian steppes. This attitude too represents a new cutural and policital feature. My article represents a preliminary exploration between coast and mountains personalities in the São Paulo state